Prediction of potential climate change impacts on the geographic distribution shift of Casuarina junghuhniana and C. equisetifolia in Southeast Asia - HASNA KHAIRUNNISA; MINI AMBARWATI KUSUMA DEWI; MUHAMMAD AMJAD HAMY FAQIIH; MUHAMMAD REYNALDY PUTRAYUDA; GILANG DWI NUGROHO; MUHAMMAD INDRAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; JATNA SUPRIATNA; ILYAS NURSAMSI; GUNAWAN GUNAWAN; PRAKASH PRADHAN; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Khairunnisa H, Dewi MAK, Faqiih MAH, Putrayuda MR, Nugroho GD, Indrawan M, Sutarno, Sugiyarto, Supriatna J, Nursamsi I, Pradhan P, Setyawan AD. 2024. Prediction of potential climate change impacts on the geographic distribution shift of Casuarina junghuhniana and C. equisetifolia in Southeast Asia. Biodiversitas 23: 6360-6371. Global warming, driven by various anthropogenic activities, leads to an increase in earth’s surface temperatures, exerting a profound influence on global climate patterns. This phenomenon significantly impacts the growth patterns of various plant species, including Casuarina equisetifolia L., commonly known as sea cypress, and Casuarina junghuhniana Miq., referred to as mountain cypress. The primary objective of this study is to assess the potential repercussions of climate change on the distribution of these two species within Southeast Asia. To achieve this goal, the study utilized the MaxEnt modeling approach, incorporating key factors such as bioclimatic conditions, soil characteristics (edaphic factors), and UV radiation levels. Present study considered three distinct time intervals (2030, 2050, and 2080) while exploring four diverse climate change scenarios (RCP 2.6, RCP 4.5, RCP 6.0, and RCP 8.5). The findings of this investigation reveal that both C. equisetifolia and C. junghuhniana are susceptible to alterations in the extent of suitable habitat distribution, which result in shifts in their geographic ranges due to evolving climatic conditions. Initially, the habitat distribution encompassed an area of only 652,819 km2, accounting for 15.65% of the suitable habitat for C. equisetifolia, and 30,132 km2, representing 0.7% of the suitable habitat for C. junghuhniana. However, by the year 2080, the habitat range for C. equisetifolia is projected to expand significantly to cover 755,082 km2 (18%) under the RCP 4.5 scenario. In contrast, C. junghuhniana is expected to experience a notable reduction, with its suitable habitat shrinking to 25,332 km2 (0.6%) under the influence of RCP 8.5. Notably, these shifts are characterized by a southeastward migration of C. equisetifolia towards Indonesian Borneo from Malaysian-Indonesian border and an eastward shift of C. junghuhniana towards the east of Sulawesi from the Gulf of Bone. These findings highlight the dynamic nature of species distributions in response to changing climatic conditions, emphasizing the need for proactive conservation efforts and adaptive management strategies to mitigate potential ecological impacts.